EDUCATION AND UTILIZATION OF MORINGA OLEIFERA TO IMPROVE THE HEALTH OF THE COMMUNITY IN LAPULU VILLAGE, ABELI DISTRICT, KENDARI CITY - Irma Irma; Harleli Harleli; Suhadi Suhadi; Yasnani Yasnani; Arum Dian Pratiwi (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2026)
Background: Moringa (Moringa Oleifera) leaves contain nutrients that make it a good choice for improving the nutritional intake of children at risk of stunting. Stunting is a growth disorder that occurs in toddlers due to chronic malnutrition, characterized by height that is not proportionate to the child's age. The Abeli subdistrict, including the Lapulu village, has the highest prevalence of stunting at 2.7%, caused by inappropriate parenting, maternal knowledge, poor food intake, and economic factors. Method: This community service activity was carried out in several phases, including: the preparation phase, implementation, such as the coordination with partners regarding the determination of time and place, as well as evaluation and assessment of the results of the activity. Results: Before the educational activities were conducted, the level of knowledge among mothers of toddlers regarding the use of Moringa Oleifera for stunting showed that 16 people (61.5%) had insufficient knowledge. However, after receiving education, the level of knowledge increased among 23 people (88.5%). Based on the Paired Sample T Test, the mean value was 4.46, and the p-value was 0.000. Therefore, it can be concluded that there was an increase in knowledge among the Lapulu Village community regarding the benefits of moringa for stunting.Conclusion: Before receiving education, the knowledge level among mothers of toddlers was low, but after receiving education, their knowledge increased. Based on the Paired Sample T Test, there was an increase in knowledge before and after receiving education